Financial Risk Management Strategies in SME International Expansion: A Systematic Review - Witantri Galuh; Giovanni Axel; Kurniasari Erika; Nurunnisa Ika Amalia (SHS Web of Conferences, 2025)
International expansion provides significant opportunities for SMEs (Small and Medium Enterprises) to improve competitiveness and expand markets. However, its implementation often faces challenges such as complex financial risks such as currency fluctuations, regulatory differences between countries, and global economic uncertainty. Unpreparedness in managing these risks can result in losses that threaten business continuity in expanding the market. This study aims to identify effective financial risk management strategies used by SMEs in the context of international expansion. Using the systematic literature review (SLR) method, this study synthesized relevant literature to answer questions regarding best practices, challenges, and knowledge gaps in financial risk mitigation strategies among SMEs. The study analysis focused on Scopus and Web of Science journal articles published in 2014-2024. The results provide insights into effective strategies in mitigating financial risks, as well as identifying factors that influence their successful implementation. The findings are expected to provide guidance for SMEs in devising more resilient financial strategies in the face of financial risks in the global market.